2021
DOI: 10.3390/su132212735
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cropland Reclamation on Ecological Security in the Yangtze River Economic Belt, China

Abstract: Ecological security is important both for maintaining the function of an ecosystem and for providing ecosystem services to the human wellbeing. The impact of land use change/cover on ecological security has attracted considerable attention, whereas the role of cropland reclamation remains unclear. The indirect loss of ecological land that occurs upon the request of cropland requisition-compensation policies offer further changes to ecological security. In order to ascertain the impact of cropland reclamation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…After analyzing the ecological barrier points, the most common type of land use is cultivated land, followed by built-up land, indicating that the main factors causing barriers to ecological migration in Chongqing are the expansion of cultivated land and urban sprawl. Current studies have less discussion on the land use of ecological barrier sites, but a large number of studies have shown that the expansion of cultivated and built-up land is the most critical factor contributing to ecological degradation, which is consistent with the results of the existing study [ 61 , 62 ]. Cultivated land has specific ecological attributes and only requires reasonable local population management.…”
Section: Discussionsupporting
confidence: 82%
“…After analyzing the ecological barrier points, the most common type of land use is cultivated land, followed by built-up land, indicating that the main factors causing barriers to ecological migration in Chongqing are the expansion of cultivated land and urban sprawl. Current studies have less discussion on the land use of ecological barrier sites, but a large number of studies have shown that the expansion of cultivated and built-up land is the most critical factor contributing to ecological degradation, which is consistent with the results of the existing study [ 61 , 62 ]. Cultivated land has specific ecological attributes and only requires reasonable local population management.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, this studied area tends to develop as the new growth center in the urban system. This also means that urban development's economic and infrastructural aspects are more critical in developing countries [19]. The productive farmland conversion tends to increase because the construction step is associated positively with spatial transformation.…”
Section: B Study Areamentioning
confidence: 99%
“…Therefore, exploring the efficiency of green use of urban land is of great practical significance to solve the problem of ecological environment improvement lagging behind urbanization development, and to promote the coordinated development of economy, society and ecology (Cui et al, 2021;Lu et al, 2022). Among China's economic regions, the Yangtze River Economic Belt is not only one of the regions with the strongest comprehensive strength and the greatest strategic support, but also a leading demonstration zone and ecological security barrier zone for ecological civilization construction, and an important position to promote the coordinated development of China's economic regions (Yin et al, 2021;Tan and Zou, 2022;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%